PELAKSANAAN PERKULIAHAN STATISTIKA DASAR DENGAN MODEL PROJECT BASED LEARNING - Rahma Siska Utari; Andinasari Andinasari; Landu Paranggi Cipta Putri; Juriah Juriah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
In digital era, students are expected to have 21st century skills to face global challenges. One of the learning models that support 21st century skills is Project Based Learning (PjBL). This research is descriptive research to describe the implementation of mathematics learning with the PjBL model in the Basic Statistics course. Fourteen students who took the Basic Statistics course were the subjects in this study. The project is a Basic Statistics project that integrates data presentation material, frequency distribution, centering measures, and data distribution measures. Data were collected using interviews, observations, self-assessment, oral presentation, peer review and final report. The implementation of learning is carried out online using google classroom, google form, zoom meeting and whatsapp group. The results of the implementation of mathematics learning with the PjBL model in the Basic Statistics course can be said to be good with an average score of 82.5. Of the fourteen students who worked on the project, five students or 36% had completed the project very well. A total of nine students or 64% have completed the math project well from the stages of planning, implementation and collecting reports. In this study, Information and Communication Technology (ICT) plays a very important role in the stages of design, implementation, and final report collection in project completion.